Social development management in the Southeast region (Vietnam) in digital transformation - Nguyen Huu Hoang; Tran Van Huan (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Social Development Management in the context of digital transformation is a new and necessary matter in Vietnam. This study is a cross-sectional study, surveying 430 officials and civil servants and 450 people in Ho Chi Minh City, Binh Duong, Tay Ninh (Vietnam) to analyze the current situation of social development management in the 6 main fields: sustainable poverty reduction; healthcare; education and training; gender equality; social safety, human security; the effectiveness and efficiency of the state of management in the context of digital transformation. The results show that both groups of participants have good and positive evaluations of social development management in these 6 (six) areas (mean â‰¥ 3.55). The ranking of social development management assessment of education, training, and healthcare in the context of digital transformation is the lowest. Chi-square correlation test on SPSS software version 25.0 shows that it is necessary to pay more attention to disadvantaged social groups to reduce inequality and digital gap when conducting social development management in the context of digital transformation (research significance, p-value < 0.05). The results of this study not only provide policy implications for localities but also suggest many in-depth research directions on this topic in the future, in the context of digital transformation.